Brain Activity and Clinical Outcomes in Adults With Depression Treated With Synchronized Transcranial Magnetic Stimulation: An Exploratory Study - Cook, Ian A.; Wilson, Andrew C.; Corlier, Juliana; Leuchter, Andrew F. (Neuromodulation (Malden, Mass.), 2019)
Background Synchronized transcranial magnetic stimulation (sTMS) imparts low‐amplitude magnetic stimulation matched to each patient's individual alpha frequency. It may act through entrainment of brain oscillations. Objectives To explore sTMS effects on neurophysiology with electroencephalography (EEG) in adults with major depressive disorder. Methods As an ancillary study to a clinical trial of sTMS, EEGs were recorded at baseline and at one and six weeks of treatment. Associations between EEG measures and clinical symptoms were examined. Results Absolute and relative power measures did not differ significantly between active and sham groups and did not change significantly over time. Changes occurring over six weeks in alpha current source density at anterior and central midline voxels were significantly correlated with changes in symptoms in subjects treated with active but not sham sTMS. Conclusion Neurophysiologic measures suggest that active but not sham sTMS engages brain targets, and that target engagement is related to treatment outcome.